1998
DOI: 10.1097/00006123-199806000-00064
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Computed Tomographic Scanner with Intraoperative and Intensive Care Unit Applications

Abstract: With these adaptations, mobile CT may increase the efficiency of intraoperative scanning by making it available to multiple operating rooms without committing it to any room for an entire operation and may increase the efficiency and safety of CT of critically ill patients who currently need to leave the intensive care unit to travel to a fixed CT installation and back.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(54 citation statements)
references
References 9 publications
0
52
0
2
Order By: Relevance
“…6,9) Intraoperative CT and MR imaging are easily integrated into navigation systems and provide excellent images of anatomical deformation in the brain. 5,15,26) However, these imaging techniques are limited by factors such as manpower, cost, and restricted surgical access. 2,7,24) US scanners have been used for intraoperative imaging for 20 years.…”
Section: Discussion I Problems Of Conventional Navigation Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,9) Intraoperative CT and MR imaging are easily integrated into navigation systems and provide excellent images of anatomical deformation in the brain. 5,15,26) However, these imaging techniques are limited by factors such as manpower, cost, and restricted surgical access. 2,7,24) US scanners have been used for intraoperative imaging for 20 years.…”
Section: Discussion I Problems Of Conventional Navigation Systemsmentioning
confidence: 99%
“…14,18,21,25) However, the accuracy of navigation systems based on preoperative imaging decreases with the progress of surgical manipulation due to a phenomenon called``brain shift,'' which is caused by various factors, including the effect of gravity on the brain, escape of cerebrospinal fluid, brain swelling, and surgical maneuvers. 7,8) Intraoperative imaging systems using computed tomography (CT) 5) or magnetic resonance (MR) imaging 15) have been introduced to counter the effects of brain shift. These intraoperative imaging systems allow update of the imaging data, but also require considerable time periods for operation.…”
Section: Introductionmentioning
confidence: 99%
“…It has scanning capabilities that allow for multiple windowing, high resolution contrasted study for soft tissue discrimination, CT angiography, and 3-D rendering capabilities. Opponent of this technology point out the risk of radiation exposure, but Butler et al showed that actual risk is quite low (7). Radiation dose report for our institutional 64 slice CT scanner is approximately 68 mGY per routine 5 mm slice head CT.…”
Section: Discussionmentioning
confidence: 93%
“…6 The Tomoscan has been evaluated for its potential applications in emergency departments, departments of surgery, and ICU settings. [14][15][16][17][18] For cranial imaging, a clinical evaluation of this machine in comparison with conventional scanners demonstrated increased noise and artifacts, but the diagnostic value was no different from that of the comparison unit. 7 When scanning patients in locations in which space is limited, gantry motion allows 356 mm of scanning length, so a head scan can be obtained without removing the patient from his or her bed.…”
Section: Tomoscan Mmentioning
confidence: 99%